Impact of Plant Spacing on Population Dynamics of Sucking Pest of Cotton - Momtaz, MB; Yeasmin, K; Khatun, MR; Ahmad, M (Journal of Environmental Science and Natural Resources, 2019)
The present study was carried out to find out the impact of plant spacing on population dynamics of sucking pest of cotton from June 2018 to February 2019. The main objectives of the study are to observe the population dynamics of jassid and whitefly under different plant population. The experiment was laid out in RCB design with three replications and five differents treatments viz.,T1- 90x45 cm T2 – 90x40 cm, T3- 90x35 cm, T4- 90x30 cm, T5 – 90X25 cm. The results revealed that peak population of jassid was recorded in last July to October and whitefly from august to October. Plant spacing showed a significant effect on the jassid population. It is clear from the results that maximum population of jassid (32.4), aphids (11.3) and whitefly (18.1) were recorded to be per leaf from those plots where minimum plant spacing (25 cm) was maintained. No of sucking insects were increasing with decreasing plant population. J. Environ. Sci. & Natural Resources, 11(1-2): 241-243 2018